Spatial behaviour of the new forms of distribution: An analysis of the metropolitan areas of Barcelona and Madrid - Raquel Insa-Ciriza (European Regional Science Association (ERSA), 1998)
In this paper I examine how affect the recent economic, politic and social changes, thus the modifications in the firms to the structure of the big cities. The appearance of technological innovations within the industry and telecommunications, the supply's increase of final products and the change in the consumers habits, have put the city into the ideal frame of economics restructuring. Nevertheless cities don't want to be only the frames of this restructuring. They want to adopt new rolls as they become a players of the same economic process by offering themselves as a city/product or city/firm. Cities assume challenges of the adaptations to the technological changes and the evolution of the productive systems. All this changes are inducing simultaneously a transformation process of the commercial activity with a strong impact on the territory. The aim of this paper is establishing an approach to the spatial dynamic of the new ways of distribution. To do so, we study the location of department stores, big supermarkets and malls in the Metropolitan Areas of Barcelona and Madrid.
Keywords: 330